Diagnostics of psychological features of emotional competence of medical students in the process of professional training - Lazurenko, O. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2018)
The model and the logic of empirical research are determined. The experimental study of emotional competence is presented. A general description of the subjects is systematized. The results of the ascertaining experiment are presented. The author conducted her research in several directions. This approach allowed the researcher to present the quantitative characteristics of emotional intelligence on all scales and subscales in details. On this basis, the author makes a detailed qualitative analysis of the manifestation of the studied ability in future doctors. Besides, after conduction of the research, the author makes conclusion that students’ ability to understand and manage other people’s emotions and the ability to understand their own emotions and manage them are not formed enough. And these make impossible the success of the future professional activities of a doctor. The author makes conclusion that the development of emotional competence of students of medical universities can be formed by introducing special courses, educational and developmental training programs into the educational process. The correlation analysis allowed the author to empirically confirm the correct determination of the content of the basic components of the future doctor’s emotional competence. Besides, it is proved that the parameters of the social, cognitive, regulatory, empathic components of emotional competence significantly correlate with each other. The received results confirmed that during first year medical students of the experimental and control groups have the same positions of the level of development of emotional competence. And any significant statistical differences in its manifestation were not found among students of the experimental and control groups. Moreover, the received results at ascertaining stage of the study showed the insufficient level of development of the components of emotional competence among students of medical faculty. This led to the creation of a program for the formation of the emotional competence of a future doctor in the process of training in a higher medical school.